Spatial predictive control using a thermal camera as feedback. (October 2017) - Wilson, Jacob; Everett, Scott; Dubay, Rickey; Parsa, Soheil S.; Tyler, Mike
Highlights: Model predictive control structure for spatially continuous sensors. Thermal camera integrated as temperature sensor in advanced control scheme. Temperature control over a continuous spacial dimension with a thermal camera. Abstract: The sensors being used in industrial settings are becoming increasingly complex and capable of acquiring significantly more data with higher functionality. One of these sensors is the thermal camera, which has the potential of capturing the spatial temperature profile of any surface. Through the extension of the conventional model-based control theory, a new model-based control scheme was formulated verify the novel concept of utilizing the spatial data from the thermal camera. To analyze this new model based control algorithm, a three zone heater barrel apparatus was designed and constructed for closed-loop testing to be performed. The experiments demonstrated the benefit of thermal camera feedback through the alterations in the control scheme. The availability of thermal profile of the system in comparison to single point temperature measurements resulted in the enhanced controller achieving better closed-loop transient responses, reduction in settling times. In addition, the use of spatial thermal images provides the possibility of controlling profiled temperature setpoints, showing the benefit and potential of using more advanced sensors in industry.